Demand & Perception Analysis of Nepal Telecoms’ Fiber-to-the- Home (NT-FTTH) Service at Myanglung Municipality Tehrathum - Dahal, Shiba Prasad (Intellectual Journal of Academic Research, 2023)
Fiber-to-the-Home (FTTH) technology has revolutionized the internet landscape by providing high-speed and reliable internet access directly to residential premises. This research aims to conduct a demand analysis of FTTH internet services to understand the factors driving consumer adoption and the potential barriers hindering its widespread implementation in Myanglung Municipality service rendered by Nepal Telecom. The study employs a mixed-method approach, combining quantitative and qualitative interviews to gain comprehensive insights into consumer preferences, perceptions, and prices related to FTTH internet. The findings from this research will contribute to a better understanding of the market dynamics and inform internet service providers and policymakers on strategies for enhancing FTTH adoption.